Analisis Evaluasi Model Cipp pada Pengelolaan Sumber Daya Manusia - Arina Manasikana; Triana Rosalina Noor (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2025)
This study aims to analyze human resource management at SDN Tambak Wedi 508 Surabaya using the CIPP (Context, Input, Process, Product) evaluation model during the 2024-2025 academic year. The research method employed is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The research subjects include the school principal, teachers, and administrative staff. The results show that: (1) Context evaluation describes the alignment of HR management programs with the school's vision, mission, and objectives; (2) Input evaluation identifies the availability of human resources, infrastructure, and budget in supporting HR management programs; (3) Process evaluation analyzes the implementation of teacher and staff competency development programs, recruitment systems, and performance evaluations; (4) Product evaluation demonstrates improvements in teacher and staff performance quality, as well as their impact on student achievement. This study recommends the need for developing continuous training programs and a more structured monitoring and evaluation system to enhance the effectiveness of HR management in schools.